Systematic review of ontology application in data quality - Mohd Jaya, Mohd Izham; Sidi, Fatimah; Affendey, Lilly Suriani; Ishak, Iskandar (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
This study presents a systematic review in investigating the adoption of ontology in managing data quality. We study a dataset of 333 paper from journals, conference proceedings and magazine to explore the motivations and limitations in adopting ontology approach to achieve high quality data. Based on the selection criteria, we then select 9 relevant papers and being discussed further in this paper. From this study, we found that ontology usage eliminated barriers of domain expert involvement in managing data quality, the heterogeneity of data source and data source schema, and also the size of database.